Scintillation Surveys, Serendipitous, Systematic and MASIV: What do they tell us - Jauncey, D.; Lovell, J.; Senkbeil, C.; Bignall, Hayley; Macquart, Jean-Pierre; Ojha, R.; Pursimo, T.; Rickett, B.; Shabala, S. (Scuola Internazionale Superiore di Studi Avanzati (S I S S A), 2007)
A variety of surveys, both serendipitous and systematic, have revealed the dramatic phenomenon of cm-wavelength refractive inter-stellar scintillation. Throughout these discoveries, the presence of accurate and reliable flux density measurements has been an essential component of progress, as have the various surveys both serendipitous and systematic